Cultivo de algas marinhas como desenvolvimento de comunidades costeiras - Bezerra, Antonino de Freitas (2008)
In northeastern Brazil, the extraction of agar has increased considerably in recent decades mainly using macroalgae of the genus Gracilaria. The pressure of the harvest of seaweed of this genus has compromised the sustainability of this natural resource. Given the current framework of decline in production of algae in the state of Rio Grande do Norte, it is necessary the deployment of crops that will assist in the development of coastal areas. This research aimed to develop studies on growth, productivity, efficiency and quality of agar of G. birdiae so as to provide subsidies for crops on commercial scale. The study was carried out in dry and rainy periods using rafts of cultivation. Algal biomass and the physical and chemical parameters of water were measured every fifteen days. In laboratory, the resistance and quality of agar were analyzed. The relative growth rate (TCR) was determined by the formula: RGR = ln (final weight / weight initial). 100 / interval time of sampling. During the study, environmental factors as salinity and temperature remained relatively constant (around 35 PSU and 28°C, respectively). The mean values of biomass ranged around 1952.67 ± 576g in the rainy period and 1925.67 ± 450g in the dry period, and they presented no significant variations. The maximum value of growth (TCR) was recorded in the dry season (7.45%.day-1), with an average over the study of 4.35%.day-1. The yield of agar ranged from 22% to 15%, and its resistance ranged from 850 to 650g. cm². The average obtained for the two periods was approximately 750 g cm². These results demonstrate the great potential of Gracilaria birdiae for mariculture can be used as an sustainable activity for coastal communities